Nutrition management programme for older adults in Ningxia nursing homes, China: evidence-based practice and the Delphi method - Haiyan Liu; Li Chen; Yanhua Ning; Yahong Guo; Weijuan Kong; Xiongxiong Lv; Meiman Li; Ting Jiang (Public Health Nutrition)
Abstract